Different Profiles of Psychological And Sociodemographic Characteristics of Mixed Martial Arts athletes - Belem, Isabella Caroline (2025)
Objective: This study represents an analysis of the association of resilience, stress, coping strategies, and sociodemographic data from Mixed Martial Arts (MMA) athletes. Methodology: Fifty Brazilian male MMA high performance athletes aged 25 ± 4.8 years participated in the study. The data were collected using a Sociodemographic questionnaire, the Connor-Davidson Resilience Scale, the Athletic Inventory of Coping Strategies, and the Athlete's Stress and Recovery Questionnaire (RESTQ-76). Analysis was conducted through cluster analysis. Results: Three distinct groups were found: Athletes from Clusters I and II proved resilient with strategies of Coping with adversity, Concentration and Coachability, showing higher scores at the following recovery scales of: success, social relaxation, general well-being, being in shape, and self-efficacy. The sociodemographic characteristics of cluster I athletes consisted of being older and having dependents, while Cluster III athletes had the lowest level of resilience, used freedom from worry strategy, and had stronger emotional stress as well as lack of energy, in addition to being younger and having no dependents. Conclusion: Considering the athletes’ characteristics, we may conclude that the level of resilience and age combined with the responsibility of having dependents can influence the use of coping strategies as well as stress in MMA athletes.